An officer and a gentleman [videorecording (DVD)] - Hackford, Taylor, 1944-; Gere, Richard, 1949-; Winger, Debra, 1955-; Keith, David, 1954-; Gossett, Louis, Jr., 1936- (Paramount, 2007)
A timeless tale of romance, friendship, and growth. Loner Zack Mayo enters Officer Candidate School to become a Navy pilot and in thirteen weeks he learns the importance of discipline, love and friendship.